The youngest student is 6 the middle student is 9 and the oldest student is 15
Explanation: first I wrote out what I know in equation form, I made y the youngest student m the middle student and o the oldest student, so we know that m-3=y and that y+3=m and that m+6=o and that finally y+m+o= 30 so then start to plug things into the bottom equation, we know y=m-3 so our equation becomes m-3+m+o=30 you simplify and you get 2m+o=33, now let’s get rid of the O for that we plug in what we know is equal to O and your left with 2m+m+6=33 you simplify that and you get m=9 now all you have to do is plug that into the equations 9-3=y and 9+6=o therefore the youngest is 6 the middle is 9 and the oldest is 15 hope this helps